2020
DOI: 10.1016/j.athoracsur.2019.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial Versus Bicaval Orthotopic Heart Transplantation: A Systematic Review and Meta-Analysis

Abstract: Background. Orthotopic heart transplantation (OHT) is the gold standard treatment in end-stage heart disease. Controversy remains whether bicaval OHT is superior to biatrial OHT in both early and late outcomes. This study aimed to provide an overview of the early and late outcomes in patients who underwent a bicaval or biatrial OHT. Methods. A systematic literature search was performed for articles published before December 2017. Studies comparing adult patients undergoing biatrial OHT and bicaval OHT were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…1,9 The difference in incidence could also be because bicaval HTs are associated with decreased early PM implantations. 15 However, one study with only bicavally transplanted recipients demonstrated a PM rate of 20.5%. 7 The authors claimed that due to the increasing donor age, the advantage of transplanting with the bicaval technique over the biatrial technique was diminished.…”
Section: Incidence Of Permanent Pacemakersmentioning
confidence: 99%
See 2 more Smart Citations
“…1,9 The difference in incidence could also be because bicaval HTs are associated with decreased early PM implantations. 15 However, one study with only bicavally transplanted recipients demonstrated a PM rate of 20.5%. 7 The authors claimed that due to the increasing donor age, the advantage of transplanting with the bicaval technique over the biatrial technique was diminished.…”
Section: Incidence Of Permanent Pacemakersmentioning
confidence: 99%
“…It is known that ischaemic time with the bicaval technique is longer than biatrial transplantation. 15 However, the fact that ischaemic time is increased during biatrial surgery could indicate a difficult procedure, which could increase the risk for damage to the conduction system. This in combination with the increased risk of sinus node ischaemia during the transplantation could explain why ischaemia is a risk factor for early PM implantation.…”
Section: Risk Factors Of Permanent Pacemakersmentioning
confidence: 99%
See 1 more Smart Citation
“…In an echocardiographic study comparing bi-caval versus atrial anastomosis technique, no effect of the technique on tricuspid regurgitation was found [ 6 ]. Several studies found that bi-caval technique decreased the post-transplant tricuspid regurgitation [ 7 – 10 ], and all patients in our study had bi-caval anastomosis.…”
Section: Discussionmentioning
confidence: 54%
“…The primary value of the analysis of a large cohort of biatrial cardiac transplant recipients reported by Hajiyev and colleagues 11 in this issue of the Journal lies in its acceptance of the propensity for distorting tricuspid annular geometry and functional TI using the biatrial technique and identifying a technical benchmark—maintaining a donor-to-recipient (D/R) right atrial anterior wall ratio <1—that mitigates this distortion by reducing tension on the anterior wall of the right atrium. The technique used by the authors' institution to achieve this benchmark appears to have resulted in a low incidence of early moderate to severe functional TI of 19%, compared with 42.8% in a contemporary pooled meta-analysis 12 and even higher rates in other series. 5 The impact of right atrial proportions on functional TI was corroborated in an earlier study by Dandel and colleagues, 13 who observed that patients without TI had a D/R atrial dimensional ratio <1, whereas those with moderate to severe TI had a D/R ratio >1.…”
mentioning
confidence: 91%